1991
DOI: 10.1093/brain/114.6.2619
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Deficit for Numbers in a Case of Dense Acalculia

Abstract: In this study we investigated the acalculic condition of a patient, C.G., with the classical signs of Gerstmann's Syndrome: finger agnosia; right-left disorientation; a profound agraphia (but with an equally profound alexia) and a remarkably dense acalculia. Using a series of number processing and number knowledge tasks, a selective impairment for numbers was demonstrated. Within the category of numbers C.G. showed a largely preserved ability to deal with numbers below 4, in all tasks and in all modalities, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(94 citation statements)
references
References 31 publications
8
82
1
3
Order By: Relevance
“…The overarching results from this rapidly growing body of research are consistent with a large body of neuropsychological evidence (Cipolotti et al, 1991;Dehaene et al, 2003). Specifically, neuroimaging research, like preceding neuropsychological studies, has suggested the bilateral parietal lobes, and specifically the bilateral intraparietal sulci, as important brain regions for processing the quantity of a discrete set of items (i.e.…”
Section: Introductionsupporting
confidence: 53%
“…The overarching results from this rapidly growing body of research are consistent with a large body of neuropsychological evidence (Cipolotti et al, 1991;Dehaene et al, 2003). Specifically, neuroimaging research, like preceding neuropsychological studies, has suggested the bilateral parietal lobes, and specifically the bilateral intraparietal sulci, as important brain regions for processing the quantity of a discrete set of items (i.e.…”
Section: Introductionsupporting
confidence: 53%
“…They are consistent with at least two previous studies. In a patient study, Cipolotti et al (1991) found that the patient had impaired number processing but intact classifier processing. Wei et al (2012) showed that quantifier processing did not rely on the IPS, but rather on the temporal and frontal cortices.…”
Section: Discussionmentioning
confidence: 99%
“…The regions of damage that lead to temporal deficits also frequently cause spatial, numerical and velocity perception deficits (e.g. Cipolotti et al 1991;Basso et al 1996;Battelli et al 2003;Becchio & Bertone 2006;Danckert et al 2007, see also Cavezian et al 2007;Zamarian et al 2007). From the point of view of ATOM, neuropsychological patient studies can be indicative of overlapping mechanisms, but the types of lesion that patients usually suffer are too large to allow structural conclusions to be drawn.…”
Section: The Role Of the Parietal Cortex In Magnitude Processingmentioning
confidence: 99%